PENGARUH MODEL WORD SQUARE TERHADAP HASIL BELAJAR IPS KELAS IV SD NEGERI 36 PONTIANAK KOTA - Mursini, Tri; Marli, Suhardi; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research was to know the effect of word square model toward learning outcomes in social studies on grade IV SDN 36 Pontianak Kota. The form of this research was a quasy experimental design with noneequivalent control group design. Population of this research is 40 students with sample 20 students class control and 20 students class experiment. To collect this data  the researcher used measuring technique which is objective  test amount to 60 question. The result of research indicate that mean of post-test experiment class equal to 70.95 and post-test control class equal to 61.9. The result examination of hypothesis use separated varians obtained tcount data post-test is equal to 2,4639 and ttabel 1,6866, which mean tcount 2,4639 > ttabel 1,6866. It means there are effect using word square model on learning outcomes social studies  fourth grade SDN 36 Pontianak Kota. From the counting effect size equal to 0,48 with criteria average. Keywords: Word Square Model, Learning Outcomes, Social Studies